Gender Association Of Restorative Techniques Performed For Class 1 Cavities In University Hospital. - K, AKSHAYA.; S, DEEPAK.; PANDURANGAN, SENTHIL MURUGAN (The journal of contemporary issues in business and government, 2021)
Restoration of carious teeth is of immense importance to avoid the progression of further sequelae of dental caries forming pulpits and causing periodontitis. This can be done either with direct restorative materials such as resin composites, amalgam or glass ionomer cements or with indirect restoration techniques such as with cast metals. Restorative material should be chosen bearing in mind all the factors influencing the properties of restorative material along with its advantages and disadvantages. Thus the aim of the current study is to evaluate the association of gender and material used for restoration among patients visiting university hospitals. All the cases reported between the month of June 2019 to March 2020 for class 1 dental caries were chosen for this study. Data of patients with class 1 caries and the type of restoration preferred were retrieved from the Dental records, Data of Patients who had class 1 caries were shortlisted and the type of restorative techniques used were analyzed, tabulated and was subjected to statistical analysis by running chi square test and P value was calculated to verify the significance of each of the variables used. From the statistical analysis it can be concluded that, direct restorative techniques were highly preferred for restoring class 1 cavities (99.65%). Of those, composite restorations (95.36%) were highly preferred than amalgam. With regard to the indirect restorative techniques, ceramic inlays were highly preferred by both the genders (56.3%). Within the limitations of the given study, patients with class 1 dental caries predominantly preferred tooth coloured restoration such as composites (direct restorative technique). Thus, there is no associated significance between gender and restorative techniques for restoring class 1 cavities.